Scalp Defect of Cranioplasty with Titanium Mesh: A Case Report - Sonbay, Antonius E.; Prasetyo, Eko; Oley, Maximillian C.; Manuhutu, Yovanka; Tjungkagi, Ferdinan (Universitas Sam Ratulangi, 2025)
Abstract: Several implant materials for cranioplasty have been studied, including autologous bone, titanium mesh, polyetheretherketone (PEEK), and polymethyl methacrylate (PMMA). Titanium mesh is believed to have excellent biocompatibility, low cost, and satisfactory cosmetic effects, especially in three-dimensional (3D) custom-made meshes. We reported a 54-year-old man complaining of open wound in his left temporoparietal region since a month. Blood tests showed leukocytosis. Patient was diagnosed as scalp infection with previous cranioplasty using bone cement on temporoparietal region. The patient underwent scalp reconstruction with skin flap, removing skin defect, and split thickness skin graft (STSG) from left thigh. Patient was provided with outpatient medication consisting of analgesics and broad-spectrum antibiotics. Follow-up assessment 14 days after surgery did not reveal any secondary infections on titanium mesh implant and skin flap. The main complications of cranioplasty, in addition to the studied aesthetic results, are represented by the risk of infection, postoperative hematoma, impaired wound healing, as well as prolonged failure due to transplant absorption or infection, as a result of which the prosthesis needs to be removed. In conclusion, titanium mesh is still a better choice of material for cranioplasty in many factors such as price, accessibility, infection rate, and biocompatibility Keywords: scalp; cranioplasty; head injury; prosthesis